Pneumonia caused by Mycobacterium kansasii in a series of patients without recognised immune defect - Arend, S.M.; de Palou, E. Cerdé; de Haas, P.; Janssen, R.; Hoeve, M.A.; Verhard, E.M.; Ottenhoff, T.H.M.; van Soolingen, D.; van Dissel, J.T. (Clinical microbiology and infection, 2004)
The clinical and epidemiological characteristics of 17 patients diagnosed with Mycobacterium kansasii pneumonia within a limited geographical region over a period of 10 years are described. An in-depth evaluation of the innate and adaptive immune systems was performed for five available patients. A comparison was made of the genetic fingerprint patterns of the isolates obtained by restriction fragment length polymorphism (RFLP) analysis, with the major polymorphic tandem repeat (MPTR) as a probe. Predisposing factors consisted of smoking, airway abnormalities, substance abuse, diabetes or poor general condition, but in two patients no risk factor was identified. In the five patients tested, no abnormalities or deficiencies were detected in the innate or adaptive type-1 immunity. All M. kansasii isolates had identical MPTR RFLP patterns, although no epidemiological connection could be established, and these were identical to those of clinical isolates from Australian patients. These data do not support the theory that defects in the innate or adaptive type-1 immunity have a role in the pathogenesis of invasive M. kansasii infections. The identical fingerprint patterns of the isolates suggested the existence of a virulent strain of M. kansasii.